Analyses of intra-annual density fluctuation signals in Himalayan cedar trees from Himachal Pradesh, western Himalaya, India, and its relationship with apple production - Maurya, Ravi S.; Misra, Krishna G.; Vishwakarma, Sadhana; Singh, Vikram; Misra, Sandhya; Yadava, Akhilesh K. (Frontiers in Forests and Global Change, 2023)
Intra-annual density fluctuation (IADF) refers to anatomical changes in the tree ring caused by a sudden change in wood density triggered by a combination of climate variations and various biotic and abiotic influences. To reveal the occurrence of IADFs, we analyze the growth rings of Himalayan cedar (Cedrus deodara) growing over the Kullu region, Himachal Pradesh, western Himalaya. Using 30 increment cores, we precisely dated and developed a 214-year-long tree-ring chronology extending back to AD 1808. The tree–growth–climate relationship using ring-width chronology and observed climate data revealed that cool and moist condition provides favorable condition for Himalayan cedar tree growth. Delving deeper into wood anatomy of growth rings, we revealed the frequent occurrences of IADFs in both earlywood (IADFe) and latewood (IADFl). The formation of IADFs in earlywood (IADFe) is related to the reduced precipitation from April to July, causing moisture stress in the soil and surrounding climate. However, wetter conditions in the late growing season, mainly August–October, activated the formation of IADFs in latewood (IADFl). The study revealed several IADF years in earlywood and latewood, such as 1901, 1902, 1903, 1914, 1915, 1919, 1920, 1923, 1925, 1943, 1958, 1959 and 1937, 1955, 1956, 1988, respectively. These IADF years corresponded with unusual climatic fluctuations that severely affected apple production, the major cash crop in the region. The analyses demonstrated that the IADF chronology of Himalayan cedar would be a valuable proxy to understand abrupt and unusual climatic fluctuations from a long-term perspective for the data-scarce western Himalayan region.